Neurophysiological Features Of Hemiballism. Issue 1 (19th May 2016) - Tai, Yi‐cheng; Yin, Yun Wo Katie; Ha, Ainhi D.; Adam, Robert; Mahant, Neil; Sue, Carolyn M.; Fung, Victor S.C.
Abstract: View Supplementary Video 1 View Supplementary Video 2 Hemiballism is a rare hyperkinetic movement disorder. The pathophysiology of hemiballism is poorly understood, and there have been few reports of neurophysiological recordings. The authors report three cases of hemiballism with associated radiological and neurophysiological findings. In patients 1 and 2, who were studied in the acute phase 4 and 14 days after presentation, irregularly timed and predominantly long‐duration electromyographic (EMG) bursts were observed typically ranging from 200 to 1500 milliseconds in duration and occurring asynchronously or alternating in antagonist muscles. In patient 3, who was studied 6 weeks after presentation when the involuntary movements had become choreiform, the EMG bursts were still from 200 to 1000 milliseconds in duration but were more synchronous or co‐contracting. The flailing movements of hemiballism appear to occur as a result of prolonged bursts of EMG activity generated in individual muscles unopposed by EMG bursting in the antagonist. During the subacute phase when the movements become more choreiform, the results indicate that EMG activity becomes more synchronous or co‐contracting. Abstract : View Supplementary Video 1 View Supplementary Video 2